Financial Signalling by Committing to Cash Outflows - Ravid, S. Abraham; Sarig, Oded H. (Journal of Financial and Quantitative Analysis, 1991)
We analyze a model in which firms signal their quality by using financial policies to commit to cash outflows. Two financial policies may be used: dividend and debt-service obligations. We find sufficient conditions for the informational equilibrium to entail concommitant use of both dividends and leverage in the cost-minimizing combination of the commitment signal. In this equilibrium, better firms pay higher dividends and are more highly levered than lower quality firms.